From the table, we were given the zero of the function h(x).
The zeros of the function are
![-3,-2,\text{ and 1}](https://img.qammunity.org/2023/formulas/mathematics/college/xsflmxuz72a095bqsbas152v6r88ebidgt.png)
The formula to obtain the equation of the function is,
![(x-a)(x-b)(x-c)](https://img.qammunity.org/2023/formulas/mathematics/college/4km6am6pj51724viiosl5tcmky3c061yb8.png)
Where
![\begin{gathered} a=-3 \\ b=-2 \\ c=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7srkom1jcxsdkavpk9blqu7mxxt1pv84b2.png)
Hence,
![\begin{gathered} h(x)=(x--3)(x--2)(x-1) \\ h(x)=(x+3)(x+2)(x-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/z1eo4p2p6rmm9iaebbhdr4kdhqefsehy9d.png)
Expanding the function above
![\begin{gathered} h(x)=x(x+2)+3(x+2)(x-1) \\ h(x)=x^2+2x+3x+6(x-1) \\ h(x)=x^2+5x+6(x-1) \\ h(x)=x(x^2+5x+6)-1(x^2+5x+6) \\ h(x)=x^3+5x^2+6x-x^2-5x-6 \\ h(x)=x^3+5x^2-x^2+6x-5x-6 \\ h(x)=x^3+4x^2+x-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/edcsy0l9kn59ldd0zu0dnchvujqqvj6c1y.png)
Therefore, the equation of the polynomial function is
![h(x)=x^3+4x^2+x-6](https://img.qammunity.org/2023/formulas/mathematics/college/i21omftotjma322hrfwv2skcca5luwy7ln.png)
Hence, the answer is Option 3.